Corrigendum: Multiplicity of Mathematical Modeling Strategies to Search for Molecular and Cellular Insights into Bacteria Lung Infection - Cantone, Martina; Santos, Guido; Wentker, Pia; Lai, Xin; Vera, Julio (Frontiers in Physiology, 2017)
[This corrects the article on p. 645 in vol. 8, PMID: 28912729.].
EVALuna2:35402
Keywords: Systems biology; Systems medicine; ODE models; Stochastic modeling; Boolean network; Agent-based modeling; Mathematical modeling; Lung infection